Adrenal extramedullary hematopoiesis, an entity to consider in the diagnosis of adrenal mass - Garazi Elorza-Echaniz; Nerea Borda-Aguirrezabalaga; Ignacio Aguirre-Allende; Ainhoa Andres-Imaz; Elisabet Bollo-Arocena; Jose Maria Enriquez-Navascues (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Extramedullary Hematopoiesis (EMH) is frequently seen in the liver, spleen or lymph nodes in patients with hematologic disorders such as beta-thallasemia or hereditary spherocytosis. We report the first case of adrenal hematopoiesis in a patient with Chronic Myelomonocytic Leukemia. The patient was a 63 year-old man who was in the study of a thrombocytopenia. A CT and MRI demonstrated a unilateral adrenal mass with multiple splenic lesions. The patient underwent right adrenalectomy and splenectomy. Microscopic examination showed extramedullary hematopoiesis in the adrenal gland and spleen. The diagnosis of extramedullary hematopoiesis must be considered in any patient with hematologic disorders and thoracic or abdominal mass. An unnecessary procedure could be avoided. Palabras clave: Extramedullary hematopoiesis; adrenal mass; adrenal incidentaloma; Chronic Myelomonocytic Leukemia.